2011
DOI: 10.1093/aje/kwr273
|View full text |Cite
|
Sign up to set email alerts
|

A Difference-in-Differences Analysis of Health, Safety, and Greening Vacant Urban Space

Abstract: Greening of vacant urban land may affect health and safety. The authors conducted a decade-long difference-in-differences analysis of the impact of a vacant lot greening program in Philadelphia, Pennsylvania, on health and safety outcomes. "Before" and "after" outcome differences among treated vacant lots were compared with matched groups of control vacant lots that were eligible but did not receive treatment. Control lots from 2 eligibility pools were randomly selected and matched to treated lots at a 3:1 rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
363
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 505 publications
(394 citation statements)
references
References 64 publications
11
363
2
5
Order By: Relevance
“…With a few exceptions, 79,91,101,104,[127][128][129] prior studies have not applied experimental or quasi-experimental approaches in testing whether urban greening affects health and safety and therefore have limited ability to establish causal mechanisms. 64 Despite implementation challenges and longer study periods, new studies should aim to provide the highest level of evidence through randomized controlled trials.…”
Section: Experimental and Mixed-methods Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…With a few exceptions, 79,91,101,104,[127][128][129] prior studies have not applied experimental or quasi-experimental approaches in testing whether urban greening affects health and safety and therefore have limited ability to establish causal mechanisms. 64 Despite implementation challenges and longer study periods, new studies should aim to provide the highest level of evidence through randomized controlled trials.…”
Section: Experimental and Mixed-methods Researchmentioning
confidence: 99%
“…64,66,78 However, one quasi-experimental study of a vacant-lot greening program in Philadelphia, PA, found an association between greened vacant lots and increased physical activity. 79 Green exposure has also been shown to prevent and mitigate stress, anxiety, and depression, [80][81][82][83] especially in urban environments. 81,84,85 Access to green views has been associated with improved mental health in general 86 and more specifically has been shown to reduce mental fatigue and improve coping with stressful settings.…”
Section: Urban Greening As Place-based Public Health Interventionmentioning
confidence: 99%
See 3 more Smart Citations